2019
DOI: 10.1039/c9cc05123f
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive and selective mercury sensor based on mismatched base pairing with dioxT

Abstract: A highly selective and sensitive sensor for mercury was designed based on a new fluorescent nucleobase, dioxT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Heavy metal ions cause well-known and extremely severe problems in the environment and in animal and human health [1,2]. Mercury(II) ions are one of the most toxic pollutants and can spread widely in the environment from industrial wastes and natural sources [3][4][5]. Moreover, Hg(II) ions can damage human organs, resulting in serious diseases such as kidney failure and brain and heart damage [6].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal ions cause well-known and extremely severe problems in the environment and in animal and human health [1,2]. Mercury(II) ions are one of the most toxic pollutants and can spread widely in the environment from industrial wastes and natural sources [3][4][5]. Moreover, Hg(II) ions can damage human organs, resulting in serious diseases such as kidney failure and brain and heart damage [6].…”
Section: Introductionmentioning
confidence: 99%
“…To further extend its applications, diox T was recently used as a metal sensor in a study where Sugiyama et al demonstrated that diox T•T and diox T•C mismatched base pairs in duplexes can serve as a nucleicacid-based mercury sensor. 338 The group of Sugiyama also investigated the possibility of using diox T as a FRET donor in combination with tC acting as an acceptor. Both were incorporated in doublestrand DNA in which the distance between the two dyes was systematically increased 339 .…”
Section: Expanded Thymine Derivativesmentioning
confidence: 99%
“…14 The highly selective and sensitive binding between diox T and metal ions allowed us to demonstrate its utility as a heavy metal sensor. 15 In parallel, 19 F-labeled nucleosides have been developed as versatile probes due to the practicality of 19 F NMR spectroscopy in investigating the structures and interactions of biomolecules. 16 Unique features, such as the intrinsic sensitivity of the 19 F nucleus and its absence from general biomolecules, make 19 F NMR probes highly attractive.…”
Section: Introductionmentioning
confidence: 99%
“… 14 The highly selective and sensitive binding between dioxT and metal ions allowed us to demonstrate its utility as a heavy metal sensor. 15 …”
Section: Introductionmentioning
confidence: 99%